2009
DOI: 10.1603/033.046.0642
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Communities Associated With Flea Vectors of Plague

Abstract: The microbial flora associated with fleas may affect their ability to transmit specific pathogens, including Yersinia pestis, and also could be used to develop paratransgenesis-based approaches to interfere with transmission. To begin addressing this hypothesis, the microbial flora associated with the relatively efficient Y. pestis vectors Xenopsylla cheopis (Rothschild) (Siphonaptera: Pulicidae) and Oropsyllamontana (Baker) (Siphonaptera: Ceratophyllidae), and the inefficient vector Ctenocephalides felis feli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Molecular phylogenetic analyses based on the 16S rRNA gene sequences revealed that the alpha-symbionts of Nysius spp., K. resedae, and other stinkbugs form a very compact monophyletic group, wherein only a few nucleotide variations are present among them. Notably, the alpha-symbiont clade also contained 16S rRNA gene sequences of uncultured bacteria derived from fleas (13) and ticks (17,44). In the Alphaproteobacteria, the alpha-symbiont clade was placed within the Rickettsiales, whose members are endocellular symbionts/parasites/pathogens such as Rickettsia, Wolbachia, Ehrlichia, Anaplasma, etc.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular phylogenetic analyses based on the 16S rRNA gene sequences revealed that the alpha-symbionts of Nysius spp., K. resedae, and other stinkbugs form a very compact monophyletic group, wherein only a few nucleotide variations are present among them. Notably, the alpha-symbiont clade also contained 16S rRNA gene sequences of uncultured bacteria derived from fleas (13) and ticks (17,44). In the Alphaproteobacteria, the alpha-symbiont clade was placed within the Rickettsiales, whose members are endocellular symbionts/parasites/pathogens such as Rickettsia, Wolbachia, Ehrlichia, Anaplasma, etc.…”
Section: Resultsmentioning
confidence: 99%
“…These bacterial lineages phylogenetically allied to "Ca. Midichloria mitochondrii" are associated with a wide range of hosts scattered throughout the eukaryotic tree of life, from arthropods, such as ticks, fleas, and stink bugs, to ciliates, amoebae, cnidarians, sponges, fish, and humans (3,9,10,11,12,13,14,15,16,17,18,19). Following Mariconti et al (15), we refer to the bacteria phylogenetically related to "Ca.…”
mentioning
confidence: 99%
“…Although geographic overlap between MDR Salmonella and Y. pestis occurs in the southwestern United States, identification of bacterial communities within fleas has failed to identify Enterobacteriaceae, suggesting that little opportunity exists for MDR enteric pathogens and Y. pestis to come into contact in this environment (6,7,13,16,17). Previous studies demonstrated that the ability of Xenopsylla cheopis fleas to transmit Y. pestis was severely compromised when the fleas were coinfected with Salmonella (8).…”
mentioning
confidence: 99%